Interleukin-4 Supports the Suppressive Immune Responses Elicited by Regulatory T Cells - Yang, Wei-Cheng; Hwang, Yih-Shiou; Chen, Ying-Yu; Liu, Chao-Lin; Shen, Chia-Ning; Hong, Wei-Hsin; Lo, Sheng-Min; Shen, Chia-Rui (Frontiers in Immunology, 2017)
Interleukin-4 (IL-4) has been considered as one of the tolerogenic cytokines in many autoimmune animal models and clinical settings. Despite its role in antagonizing pathogenic Th1 responses, little is known about whether IL-4 possesses functions that affect regulatory T cells (Tregs). Tregs are specialized cells responsible for the maintenance of peripheral tolerance through their immune modulatory capabilities. Interestingly, it has been suggested that IL-4 supplement at a high concentration protects responder T cells (Tresps) from Treg-mediated immune suppression. In addition, such supplement also impedes TGF-β-induced Treg differentiation in vitro. However, these phenomena may contradict the tolerogenic role of IL-4, and the effects of IL-4 on Tregs are therefore needed to be further elucidated. In this study, we utilized IL-4 knockout (KO) mice to validate the role of IL-4 on Treg-mediated immune suppression. Although IL-4 KO and control animals harbor similar frequencies of Tregs, Tregs from IL-4 KO mice weakly suppressed autologous Tresp activation. In addition, IL-4 deprivation impaired the ability of Tregs to modulate immune response, whereas IL-4 supplementation reinforced IL-4 KO Tregs in their function in suppressing Tresps. Finally, the presence of IL-4 was associated with increased cell survival and granzyme expression of Tregs. These results suggest the essential role of IL-4 in supporting Treg-mediated immune suppression, which may benefit the development of therapeutic strategies for autoimmune diseases.